Loving water across religions contributions to an integral water ethic - McAnally, Elizabeth ca. 20./21. Jh (Ecology and justice, 2019)
"McAnally presents an academically rigorous, spiritually rich approach to the myriad global issues related to water. The author draws from Christianity's sacramental consciousness of baptism, loving service of the Yamuna River in Hinduism, and the compassionate wisdom of the bodhisattva to develop 'an integral approach to water ethics.' Building on but distinct from the foundation laid by Christiana Zenner's Just Water, this book is a welcome addition to the growing field of concern surrounding global water crises"...